PENDIDIKAN HIV/AIDS UNTUK REMAJA: MENGURANGI STIGMA DAN MENINGKATKAN PENGETAHUAN : HIV/AIDS Education for Teenager: Reducing Stigma and Increasing Knowledge - Wahyudi*, Gufron; Raharjo, Rahmawati (Forind Press, 2024)
Currently, HIV/AIDS is not only suffered by people of productive age or adults, but can also affect children and teenagers. Adolescents are an age group that is very vulnerable to contracting HIV/AIDS and is susceptible to negative stigma towards PLWHA due to ignorance about HIV/AIDS. The aim of this community service activity is to increase youth knowledge about HIV/AIDS and build a positive stigma attitude towards ODHA. This activity was carried out using the lecture method and giving pre-tests and post-tests to determine the effectiveness of health education. The results of educational activities show that health education about HIV/AIDS for teenagers is effective in increasing knowledge and changing the negative stigma towards ODHA into a positive one, marked by differences in knowledge about HIV/AIDS and stigma attitudes before and after the presentation of the material